2013
DOI: 10.4321/s1886-58872013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Distorções acerca do testamento vital no Brasil (ou o porquê é necessário falar sobre uma declaração prévia de vontade do paciente terminal)

Abstract: ARTÍCULODistorções acerca do testamento vital no Brasil (ou o porquê é necessário falar sobre uma declaração prévia de vontade do paciente terminal)Distortion on living will in Brazil (or why it is necessary to talk about a prior declaration of will of terminal patient) AbstractThis article aims to analyze the panorama of the Brazilian discussion concerning to the living will, focusing at the controversial issues, and the very often divergent views about the subject. First, it focuses at the question of termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
26

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 3 publications
0
12
0
26
Order By: Relevance
“…Patience Self Determination Act (PSDA), traduzido como Lei de Autodeterminação do Paciente, sendo que, a partir desta legislação emergiram debates, tanto públicas, como privadas, que forçaram a confrontar as decisões de final de vida 2 . Apesar do Brasil ainda não ter uma legislação federal normatizando as DAV, em 31 de agosto de 2012 o Conselho Federal de Medicina (CFM) aprovou a Resolução n° 1.995, na qual se atesta a vontade do paciente em fim de vida sobre os tratamentos médicos, a designação de um interlocutor para tal fim, além do dever do médico em cumprir o desejo do paciente terminal.…”
unclassified
“…Patience Self Determination Act (PSDA), traduzido como Lei de Autodeterminação do Paciente, sendo que, a partir desta legislação emergiram debates, tanto públicas, como privadas, que forçaram a confrontar as decisões de final de vida 2 . Apesar do Brasil ainda não ter uma legislação federal normatizando as DAV, em 31 de agosto de 2012 o Conselho Federal de Medicina (CFM) aprovou a Resolução n° 1.995, na qual se atesta a vontade do paciente em fim de vida sobre os tratamentos médicos, a designação de um interlocutor para tal fim, além do dever do médico em cumprir o desejo do paciente terminal.…”
unclassified
“…Patient must have met his desires and aspirations, as well a manifestation of respect to his autonomy and dignity when he is not capable of expressing them clearly and sensibly. In the other hand, should be guaranteed to doctor that, when attending expressly patient's will, he won't be able to suffer sanctions in legal framework or by his professional entity 32 . Patient's right of expressing and having satisfied his desires must be linked to immunity warranty to medical staff as agreeing in suspending disproportional or futile therapeutic measures intended for terminally ill patients without recovering perspectives, so following expressly patient's will.…”
mentioning
confidence: 99%
“…So, the criminal imputability guarantee must be clearly and formally discriminated even in medical profession code or in any other laws referring to this subject 32 . Regarding to this matter, another study suggests the adoption of actions to offer a death worthy to patient: respect to his will, criminal immunity to medical staff, decriminalization of any aid for dying and punishment for therapeutic obstination.…”
mentioning
confidence: 99%
“…However, this resolution does not resolve a number of controversies that relate to this subject: the applicability of ADW; the expectation that final decisions will correspond to peoples' wishes; the insertion of health professionals into the ADW process; and whether the patients' decisions can be changed, among other questions (6) . Studies in Brazil have shown that doctors have difficulty respecting a patient's will, even when it is written, if the family opposes that will (7) .…”
Section: Introductionmentioning
confidence: 99%